2010
DOI: 10.1111/j.1540-6040.2009.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structuring of Urban Life in a Mixed–Income Housing “Community”

Abstract: Developing mixed-income communities has drawn increased attention from sociologists and other researchers in recent years, generating sharp debates over equitable access, the nature of community, and the role of policy. Debates over social relations and social influence in mixed-income communities have often overlooked what formal institutions-as opposed to race, class, and other predictors of informal neighboring-contribute to social life. This study uses ethnographic fieldwork, document analysis, and semistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 38 publications
(92 reference statements)
4
47
1
1
Order By: Relevance
“…This perspective concurs with the idea of social mix as a means to enhance social capital through participation in local organisations and initiatives with common meetings, shared norms and activities that encourage positive social relations and bonds between members of different groups (Graves 2010;Tach 2009). This was similar to the findings of Allen et al (2007) in two middle class neighbourhoods, which found that the 'spoiled identity' of social housing tenants was managed through middle class residents emphasising the similarities rather than differences between them.…”
Section: Private Residents' Views and Experiences Of Social MIXsupporting
confidence: 67%
“…This perspective concurs with the idea of social mix as a means to enhance social capital through participation in local organisations and initiatives with common meetings, shared norms and activities that encourage positive social relations and bonds between members of different groups (Graves 2010;Tach 2009). This was similar to the findings of Allen et al (2007) in two middle class neighbourhoods, which found that the 'spoiled identity' of social housing tenants was managed through middle class residents emphasising the similarities rather than differences between them.…”
Section: Private Residents' Views and Experiences Of Social MIXsupporting
confidence: 67%
“…Beginning more than a decade before the advent of HOPE VI, three public housing projects in Boston-Commonwealth, West Broadway and Franklin Field-underwent substantial renovation and rehabilitation, while maintaining their status as housing solely for low-income households (Vale, 2002). Similarly, Boston's other HOPE VI redevelopment efforts-at Mission Main, which started before Orchard Park, as well as Maverick Landing which came later-each rehoused low-income public housing residents as the overwhelming majority in the completed developments; subsequent BHA HOPE VI efforts eschewed a market-rate component entirely (Curley, 2010;Graves, 2010;Tach, 2009). Surprisingly, most analysts have overlooked the experience of residents at Orchard Gardens and other redeveloped communities that have similarly kept a majority of low-income households.…”
Section: Discussion-hoping For Morementioning
confidence: 97%
“…A few early studies noted the potentially positive aspects of redevelopment for residents regarding housing quality and living conditions (Joseph, 2008;. Most attention has focused on the limited social interaction with higher income neighbours, compared to those of similar socio-economic backgrounds, which may be due to social stigma, differential treatment by building management and demographic differences (Brophy & Smith, 1997;Chaskin & Joseph, 2015;Clampet-Lundquist, 2004;Graves, 2010;Kleit, 2005;Tach, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Typically, these units do not provide the accessibility or services individuals desire (Smith & Ferryman, 2006). In many accounts, management is characterized by constant supervision and policing of existing public housing tenants (Graves, 2010;Hackworth, 2005). Furthermore, the management of vulnerable populations has resulted in inequitable treatment in housing provision.…”
Section: Neighborhood and Communitymentioning
confidence: 99%